CRS stack based seismic imaging – a case study from St Ives mining camp, Kambalda, Western Australia - Malovichko, Liliya; Urosevic, Milovan (CSIRO, 2013)
Seismic exploration in hard rock environments is challenging due to complex geological conditions that reduce the signal-to-noise (S/N) ratio of seismic data and, thus, an accurate velocity model recovery likelihood. This limits the application of conventional imaging methods, e.g., normal moveout (NMO), dip moveout (DMO) stacking or pre-stack migration. The common reflection surface (CRS) stacking technique can be used in complex environments to increase the fold and therefore the signal quality and produces reliable stacked sections with high resolution. On the other hand, CRS stacking approach does not depend on a velocity model. The CRS stacking approach was applied to 2D and 3D datasets acquired across the St Ives mining camp in Kambalda, Western Australia located within the core of a regional-scale Kambalda Dome. The main objective of this study is to review the application of the CRS approach at the St Ives mining camp in Kambalda, Western Australia. Stacked 2D seismic sections and a 3D seismic volume obtained using the CRS approach are superior to those obtained by conventional DMO/NMO processing. They are characterized by a higher S/N ratio and improved continuity of seismic reflection events. Parameters (wavefield attributes) estimated using the CRS approach have a clear geophysical interpretation and will be used for building velocity models. The target area and the existing faults and fractures were imaged clearly and the high grade of tectonic displacement necessary to ensure a sufficiently large production rate was verified. The CRS approach is now adopted as a part of the standard processing flow for hard rock seismic.